PEMANFAATAN LIMBAH DAUN KAYU PUTIH SEBAGAI ELEKTRODA KAPASITOR - Saiful Kuswandi; Hasan Bashori; Miftahul Huda (Prodi Teknik Mesin Universitas Yudharta, 2022)
A capacitor is an electronic device or component that can function in the business of storing electric charge consisting of two conductors separated by an insulating material/dielectric in each conductor, or what is usually called a chip. Capacitors are devices that can store energy as well as batteries. Eucalyptus leaves are a source of raw materials for the needs of the community that can be made capacitor electrodes. The purpose of this study was to make capacitor electrode materials by utilizing activated carbon and eucalyptus leaf waste and to determine the current and voltage generated from capacitor electrodes with activated carbon and eucalyptus leaf waste using an oscilloscope and avometer. Experimental research method, data collection by testing materials. The results of the research carried out can produce the highest voltage value at a 1:1 material ratio of 0.040V and the lowest at a 1:1 material ratio of -0.044V. While the results of the highest current value at 1:2 material ratio of 0.98A, the lowest at 1:1 material ratio of 0.02A.